Associations of Monocytes and the Monocyte/High-Density Lipoprotein Ratio With Extracranial and Intracranial Atherosclerotic Stenosis - Liu, Zhu; Fan, Qingli; Wu, Shizheng; Lei, Yancheng (Frontiers in Neurology, 2021)
I am pleased to submit an article entitled “Association of monocytes and the monocyte/high-density lipoprotein ratio with intracranial and extracranial atherosclerotic stenosis” by Zhu Liu and colleagues for consideration for publication as a Clinical and Population Research Paper in Frontiers in Neurology. Frontiers in Neurology leads to pathophysiological changes, such as lumen stenosis, that are important risk factors for ischaemic cerebrovascular diseases, and inflammatory mechanisms are thought to play an important role in its development. The monocyte/high-density lipoprotein ratio (MHR) is a potential inflammatory marker associated with coronary stenosis and myocardial infarction. In this study, we aimed to establish a reliable theoretical basis for the relationship between MHR and stenosis to guide the prevention and treatment of intracranial and extracranial arterial stenosis. To accomplish this, we retrospectively included patients with intracranial and/or extracranial Brain Research on digital subtraction angiography (DSA), grouped them by the degree and location of stenosis, and compared their clinical baseline data and laboratory indexes. We found that MHR ×102(odds ratio (OR)=1.119, P<0.001), age (OR=1.057, P=0.007), and lymphocyte (OR=0.273, P=0.002) could significantly affect cerebral atherosclerotic stenosis, the AUC (area under the ROC curve) of MHR was 0.82, and the optimal diagnostic value was 0.486. Further analysis of the mild, moderate, and severe stenosis groups showed that MHR ×102 (OR=1.07, P<0.001) significantly affected the severity of stenosis in patients. (2) According to the analysis of stenosis at different sites, the rate of extracranial artery stenosis in patients who smoked (OR=3.86, P=0.023) and had a reduced lymphocyte level (OR=0.202, P=0.001) was significantly higher than that in patients who smoked (OR=3.86, P=0.023). With increasing age, the rate of extracranial and extracranial artery stenosis increased significantly. With the increase in MHR level, the stenosis rate of each group was significantly higher than that of the non-stenosis group. We believe that this manuscript is appropriate for publication in Frontiers in Neurology because our findings improve our understanding of the relationship between brain research and inflammation. Furthermore, the predictive value of MHR can facilitate consequent treatment decisions in clinical settings, providing a possible alternative to cerebrovascular DSA, which is traumatic, risky, and costly.